Peranan Filsafat Hukum Dalam Perlindungan Anak di Indonesia - Simatupang, Rajarif Syah Akbar (EduYustisia, 2024)
The Indonesian state has responsibility for the welfare of children constitutionally in the 1945 Constitution of the Republic of Indonesia. Hierarchically, various legal products were issued and ratified which became the basis for policies and regulations in child protection in Indonesia. Child protection already has national legal products and international legal products which have been ratified by Indonesia. Children's rights are part of human rights contained in the 1945 Constitution of the Republic of Indonesia and the United Nations Convention on the Rights of the Child. The research method used is normative juridical research, namely legal research carried out by examining library materials or secondary data. The concept of a rule of law based on Pancasila certainly upholds and pays attention to human and national values, and because naturally children are the most vulnerable human figures in terms of defending their own safety and interests, and are vulnerable to becoming victims of interference from other human beings who have more Being an adult and being strong first is synonymous with legal protection for children, and this is also reflected in the constitution. Legal Philosophy studies the nature of seeking justice. Legal philosophy is a philosophy or part of philosophy that directs (focuses) its reflection on law or legal phenomena. Legal philosophy is not aimed at questioning certain positive laws, but rather at reflecting on law in its generality or law as such.